Makna Kata Rupa pada Ungkapan Paralel μορφῇ Θεοῦ dan μορφὴν δούλου dalam Filipi 2:6-7 - Andreas Kurniawan Purnomo; Ken Jacks Gunawan Waoma; Andreas Danang Rusmiyanto (Jurnal Teologi Gracia Deo, 2023)
This article discusses the many discussions regarding the nature of Jesus Christ and the circulation of false teachings regarding His divinity. This article discusses the meaning of the word like in the parallel expressions μορφῇ Θεοῦ (morphe Theou or the likeness of God) and μορφὴν δούλου (morphen doulou or the likeness of a servant) in Philippians 2:6-7. By conducting qualitative and hermeneutic research, this research aims to provide clear and relevant information for all believers today, which is often poorly understood by some people and groups. This word is often used to build the assumption that Jesus is only like or similar to God, but Jesus himself is not God. This view contradicts the Christian faith, which recognizes Jesus as God. This article presents a complete discussion regarding the meaning of the word μορφῇ (morphe or appearance) in the text Philippians 2:6-7. From the research results, it was found that the word "likeness" in the parallel phrases "likeness of God" and "likeness of a servant" does not need to be interpreted as something natural or abstract but is Paul's ontological statement regarding the divinity of Jesus as well as the humanity of Jesus Christ. AbstrakArtikel ini membahas banyaknya diskusi mengenai natur Yesus Kristus serta beredarnya pengajaran yang keliru mengenai keilahian-Nya, artikel ini membahas makna kata rupa dalam ungkapan pararel μορφῇ Θεοῦ (morphe Theou atau rupa Allah) dan μορφὴν δούλου (morphen doulou atau rupa seorang hamba) dalam Filipi 2:6-7. Dengan melakukan penelitian secara kualitatif dan hermeneutik, penelitian ini bertujuan untuk memberikan suatu informasi yang jelas dan relevan bagi semua orang percaya di masa kini yang seringkali kurang dipahami oleh sebagian orang maupun kelompok. Kata ini seringkali digunakan untuk membangun asumsi bahwa Yesus hanya serupa atau mirip dengan Allah, tetapi Yesus sendiri bukanlah Allah. Pandangan ini jelas bertentangan dengan iman Kristen yang mengakui Yesus sebagai Allah. Artikel ini menyajikan pembahasan yang utuh mengenai makna kata μορφῇ (morphe atau rupa) dalam teks Filipi 2:6-7.  Dari hasil penelitian didapati bahwa kata “rupa” dalam frasa paralel “rupa Allah” dan “rupa seorang hamba” tidak perlu ditafsirkan sebagai sesuatu yang nyata maupun abstrak, melainkan sesungguhnya merupakan pernyataan ontologis Paulus mengenai keilahian Yesus sekaligus kemanusiaan Yesus Kristus.